50 years of the Applied Probability Trust, 1964–2014. (December 2014) - Gani, Joe
Abstract : 2014 marks the fiftieth anniversary of the Applied Probability Trust (APT), an event celebrated by the present volume. This article sketches the APT's history from its beginnings in 1964 to the present.